(untitled) (Research, Society and Development, 2026)
Introduction: Chronic kidney disease (CKD) is a disease that causes progressive and irreversible loss of kidney function, representing a global public health problem. Objective: To characterize the epidemiological profile of CKD in the state of Pernambuco from 2017 to 2022. Method: This is a quantitative, ecological, and descriptive time-series study using descriptive statistics with line graphs, column graphs, data classes, mean and standard deviation values, and statistical analysis of hospitalizations, deaths, and the quantity/expenses for hemodialysis collected from DATASUS. The variables were sex, race, and age group, and the data were analyzed for normality and presented as total, mean, and standard error. Results: Pernambuco had the seventh highest annual average in the Northeast for hospitalizations and hemodialysis. There were differences in hospitalizations across all age groups, with a prevalence among non-white men. Deaths and expenses for general hospital services were prevalent among non-white adult men. Hemodialysis costs and numbers were higher in men, and this difference was not observed with regard to race. Conclusion: This study highlights a profile of chronic kidney disease (CKD) incidence and access/hospital costs higher in non-white men. The mortality profile differs between pediatric and adult age groups, possibly due to the origin of CKD and its progression. However, after age 20, men are primarily responsible for high rates of hemodialysis and related costs, and non-white men die more frequently. These findings support more equitable health policies and broaden the basis for research on social and biological factors in CKD progression.